Numerical Modelling Analysis for Carrier Concentration Level Optimization of CdTe Heterojunction Thin Film–Based Solar Cell with Different Non–Toxic Metal Chalcogenide Buffer Layers Replacements: Using SCAPS–1D Software - Samer H. Zyoud; Ahed H. Zyoud; Naser M. Ahmed; Atef F. I. Abdelkader (Crystals, 2021)
Cadmium telluride (CdTe), a metallic dichalcogenide material, was utilized as an absorber layer for thin film–based solar cells with appropriate configurations and the SCAPS–1D structures program was used to evaluate the results. In both known and developing thin film photovoltaic systems, a CdS thin–film buffer layer is frequently employed as a traditional n–type heterojunction partner. In this study, numerical simulation was used to determine a suitable non–toxic material for the buffer layer that can be used instead of CdS, among various types of buffer layers (ZnSe, ZnO, ZnS and In2S3) and carrier concentrations for the absorber layer (NA) and buffer layer (ND) were varied to determine the optimal simulation parameters. Carrier concentrations (NA from 2 × 1012 cm−3 to 2 × 1017 cm−3 and ND from 1 × 1016 cm−3 to 1 × 1022 cm−3) differed. The results showed that the use of CdS as a buffer–layer–based CdTe absorber layer for solar cell had the highest efficiency (%) of 17.43%. Furthermore, high conversion efficiencies of 17.42% and 16.27% were for the ZnSe and ZnO-based buffer layers, respectively. As a result, ZnO and ZnSe are potential candidates for replacing the CdS buffer layer in thin–film solar cells. Here, the absorber (CdTe) and buffer (ZnSe) layers were chosen to improve the efficiency by finding the optimal density of the carrier concentration (acceptor and donor). The simulation findings above provide helpful recommendations for fabricating high–efficiency metal oxide–based solar cells in the lab.